(3,6-Dimethoxynaphthalen-2-yl)(naphthalen-2-yl)methanone - Tsumuki, Takehiro (International Union of Crystallography, 2012)
In the title compound, C(23)H(18)O(3), the dihedral angle between the two naphthalene ring systems is 78.02 (3)°. The bridging carbonyl C—C(=O)—C plane makes a dihedral angle of 70.56 (5)° with the naphthalene ring system in the 2,7-dimethoxynaphthalene moiety and a dihedral angle of 11.53 (5)° with the naphthalene ring system in the naphthoyl group. In the crystal, adjacent molecules are linked via C—H⋯π interactions, forming chains along [010].